2000
DOI: 10.1046/j.1464-5491.2000.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic status, obesity and prevalence of Type 1 and Type 2 diabetes mellitus

Abstract: The study confirms the relationship between deprivation and the prevalence of Type 2 diabetes. There are more obese, diabetic patients in deprived areas. They require more targeted resources and more primary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
5
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(195 citation statements)
references
References 6 publications
14
172
5
4
Order By: Relevance
“…This result contrasts sharply with the significant effect of diabetes on mortality in a population of older diabetic people that included newly diagnosed individuals and those with a longer duration of disease (5). Studies that have found small differences in mortality, even in men diagnosed at a later age, have not adjusted for the confounding effect of deprivation (possibly independently associated with diabetes prevalence [13] and mortality).…”
Section: Research Design and Methods -The Darts/memo (Diabetes Audit mentioning
confidence: 81%
“…This result contrasts sharply with the significant effect of diabetes on mortality in a population of older diabetic people that included newly diagnosed individuals and those with a longer duration of disease (5). Studies that have found small differences in mortality, even in men diagnosed at a later age, have not adjusted for the confounding effect of deprivation (possibly independently associated with diabetes prevalence [13] and mortality).…”
Section: Research Design and Methods -The Darts/memo (Diabetes Audit mentioning
confidence: 81%
“…Further, regional socioeconomic conditions were assessed from a broad spectrum of socioeconomic indicators taken from annually updated official statistics for the total population or from a standardised, continuous household sample survey (the German Microcensus). Thus, in contrast to many other ecological studies based on census data covering only a short period [9,10,12,17,19,21,26,27], our socioeconomic data covered a reasonable time span.…”
Section: Discussionmentioning
confidence: 96%
“…In Germany, as in other European countries, the growing social inequality among children is a serious problem [6]. Epidemiological studies on the association between social status and type 1 diabetes in children have reported conflicting results, finding positive [7][8][9][10][11][12][13][14][15][16][17], inverse [18][19][20][21][22][23][24][25] or no associations [26][27][28]. Likewise, the results of studies on the relation with population density and with urban versus rural areas are contradictory [10,13,14,17,19,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Of the lifestyle factors, obesity is a public health concern globally and is shown to be highly prevalent in socioeconomically deprived areas of the population in the United Kingdom (30). Obesity is also known to cluster with several risk factors and markers suggested to be causally related with CKD and an independent predictor of CKD in the population (31).…”
Section: Discussionmentioning
confidence: 99%